Subpopulations of blood monocytes in patients with generalized hypoxia - S. P. Chumakova; M. V. Vins; O. I. Urazova; D. A. Azarova; V. M. Shipulin; A. S. Pryakhin; E. B. Bukreeva; A. A. Bulanova; A. P. Koshel; E. G. Churina; A. V. Sitnikova; N. P. Garganeeva; et al. (Бюллетень сибирской медицины)
The aim of the work is to establish general regularities and features of differentiation of blood monocytes into 4 subpopulations in diseases associated with circulatory and respiratory hypoxia.Materials and methods. 18 patients with ischemic heart disease (IHD), 12 patients with ischemic cardiomyopathy (ICMP), 14 patients with chronic obstructive pulmonary disease (COPD), 15 patients with newly diagnosed infiltrative pulmonary tuberculosis (PTB) and 12 healthy donors were examined. In whole blood, we determined the relative number of different subpopulations of monocytes by flow cytometry. The results were analyzed by statistical methods.Results. It is shown that an increase in the number of classical (80.56 [77.60; 83.55]%) and the deficit of intermediate (10.38 [9.36; 11.26]%), non-classical (6.03 [5.24; 6.77]%) and transitional (2.14 [1.41; 3.92] %) monocytes in the blood is determined in patients with COPD when compared with the group of healthy donors (p < 0.05). In groups of patients with PTB and IHD, an increase in the number of intermediate monocytes (26.24 respectively [22.38; 42.88] % and 25.27 [15.78; 31.39]%) and the lack of transitional cells (1.77 [1.36; 3.74]% and 2.68 [2.63; 4.0]%) at the normal content of classical and non-classical forms of monocytes (p < 0.05) is detected. In patients with ICMP, a decrease in the number of non-classical monocytes (up to 5.05 [4.08; 6.58]%) is combined with the normal cell content of other subpopulations (p < 0.05). The interrelation between the number of classical and intermediate monocytes in patients with COPD (r = –0.63; p < 0.05), PTB (r = –0.72; p < 0.01), IHD (r = –0.59; p < 0.05), ICMP (r = –0.58; p < 0.05) was established.Conclusion. In COPD associated with generalized hypoxia, an increase in the number of classical monocytes is combined with a deficiency of their other subpopulations in the blood. In PTB and IHD, antigenic stimulation of the immune system mediates accelerated differentiation of monocytes from classical to intermediate forms with a decrease in the number of transitional cells regardless of the etiology of the disease (infectious or non-infectious) and the type of hypoxia (respiratory or circulatory).